Imperatives for Transformation of the International Monetary System in the Conditions of Multipolarity - A. V. Kuznetsov (Финансы: теория и практика, 2022)
The neoliberal model of globalization promoted the outstripping growth of financial assets over the development of the real sector. The functioning of the international monetary system (IMS), based on one key national currency — the US dollar, has led to the financialization of the world economy and the formation of global imbalances. The purpose of the article is to substantiate the need to replace US-centric financial institutions with new institutions at the regional level and to transform the IMS in the direction of monetary polycentrism and regionalization. The paper discusses the mutual responsibility of the core and periphery countries for the formation of global imbalances. The financial and economic indicators of sovereign states, transnational companies and transnational banks are compared according to the “scale” of globalization. The study shows chronic disproportions between the dynamics of global capital growth and economic growth rates, leading to the state’s loss of control over the reproduction process. It is substantiated that the current transformation of the IMS in the direction of monetary polycentrism and regionalization is a natural reaction to these imbalances. The article reveals a negative relationship between the implementation of procyclical and anti-crisis monetary policies by the central banks of developed countries and the competitive positions of developing countries in international financial and commodity markets. The factors of using the oligopoly of the Big Three credit rating agencies as a “soft power” to maintain the US global hegemony and the status of the US dollar as a key reserve currency are systematized. The author concludes that in order for developing countries to form their own international liquidity, it is necessary to stimulate the internationalization of their currencies by developing pan-Asian financial institutions and encouraging competition between them and the existing institutions of the IMS.